Effects of packaging parameters on the inactivation of Salmonella contaminating mixed vegetables in plastic packages using atmospheric dielectric barrier discharge cold plasma treatment. (February 2019) - Kim, Su Yeon; Bang, In Hee; Min, Sea C.
Abstract: Effects of packaging parameters on the inactivation of Salmonella contaminating mixed vegetables in plastic packages using atmospheric dielectric barrier discharge cold plasma treatment (ADCPT) were investigated. The inactivation rate of indigenous aerobes of grape tomatoes in low density polyethylene packaging (1.2 log CFU/tomato) was higher than that in polyethylene terephthalate packaging (0.8 log CFU/tomato). Increasing oxygen concentration in the package headspace by 85% did not affect the Salmonella reduction rate. However, an increase in the volume ratio of headspace to sample from 30:1 to 43:1, a change from indirect treatment to direct treatment, and the use of secondary packaging led to an increase in the Salmonella reduction rates by 1.2, 2.3, and 0.7 log CFU/tomato, respectively. The water vapor permeability of the tested packages increased after ADCPT by 16.7–41.7%, while tensile properties, transparency, glass transition temperature, and surface morphology did not change. Differences in inactivation effects according to package shape were eliminated by shaking during treatment. The results demonstrated the packaging parameter-dependent efficacy of in-package ADCPT and effective ADCPT for mixed vegetable decontamination with minimal package property modification. Highlights: Atmospheric cold plasma (ACP) decontaminates mixed vegetables in plastic containers. Effective container parameters include the kinds of plastics and package shape. Effective treatment parameters are container shaking and sample–electrode distance. Other key parameters are secondary packaging and headspace-sample volume ratio.